Higher yield and economic benefits are achieved in the macadamia crop by irrigation and intercropping with coffee - Perdona, Marcos J.; Soratto, Rogerio P. [UNESP] (Elsevier B.V., 2015)
The main difficulty in expanding macadamia (Macadamia integrifolia Maiden &Betche) cultivation is the high payback period, which is caused by low yields and the long juvenile period. The use of technologies such as intercropping and irrigation has been suggested as a solution for this problem. For seven years, an experiment was conducted in the sao Paulo State, Brazil, to evaluate the growth and yield of a macadamia crop and to analyze the profitability and payback period of the investment represented by these technologies. Treatments consisted of two cropping systems (macadamia monocropping and macadamia-Arabica coffee (Coffea arabica L.) intercropping) and two water regimes (without (rainfed) or with drip irrigation) and were replicated ten times. Drip irrigation and intercropping with coffee provided the greatest growth and an earlier production of macadamia. Compared with that of rainfed macadamia monocropping, the kernel yields were 51, 176, and 251% higher in the rainfed macadamiacoffee intercropping, irrigated macadamia monocropping, and irrigated macadamia-coffee intercropping treatments, respectively. Irrigation also increased the yield of coffee intercropped with macadamia; thus, the income from this cropping system was more increased. Irrigation and intercropping with coffee reduced the payback period of the macadamia crop investment. The highest profitability was achieved using both irrigation and the intercropping of macadamia with Arabica coffee. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Macadamia integrifolia; Coffea arabica; Drip irrigation; Macadamia-coffee intercropping; Water deficit; Profitability